Consumer Protection for Bank Customers in Standard Clause Agreements - Burhanuddin, Sitti Khairunisa; Fuad, Fokky; Rohaya, Nizla; Machmud, Aris (Universitas Muhammadiyah Tangerang, 2024)
A standard agreement is a legally binding document containing pre-formulated clauses that govern the relationship between banks and their customers. Although regulated by the Consumer Protection Act No. 8 of 1999, such agreements can unilaterally place customers in vulnerable positions, necessitating legal safeguards to ensure customer security and prevent potential harm. This study employs an empirical legal research method, analyzing how laws are applied in society by focusing on public behavior through the distribution of questionnaires. Based on the collected data, customer rights are generally well-protected, as indicated by respondents' high level of trust in banking institutions to safeguard their funds. Furthermore, a low number of respondents reported experiencing losses due to standard agreement clauses, resulting in few complaints to banks, regulatory institutions, or authorities.Keywords: Consumer Protection, Standard Agreement, Banking